Mapping intellectual structure of ownership structure and corporate social responsibility: a bibliometric analysis - Gibson Munisi (Cogent Business & Management, 2024)
Corporate social responsibility(CSR) continues to be important to researchers, practitioners, and policymakers. This is evidenced by the increasing number of publications and attention given to this topic. Furthermore, it is widely recognised that a firm's internal corporate governance, including ownership structure, can impact CSR strategies implemented by the firm. Consequently, research on ownership structure and CSR is indispensable. However, no systematic and comprehensive review of studies in this area has been conducted to assess the current state and future research direction. Therefore, this study employs the bibliometric method to provide an overview of the literature and identify potential research directions in ownership structure and CSR. This study aims to provide an overview of the development of ownership structure and CSR literature and identify the most productive authors, most influential articles, most influential journals, most productive countries, and the most predominant keywords to establish current status and show future research avenues. This study uses bibliometric analysis to review the literature on ownership structure and CSR based on 1,046 articles published from 1980 to February 2023 in Scopus–indexed journals. Findings indicate the most productive authors, most influential articles, most productive and influential countries, and most predominant keywords in ownership structure and CSR research. Moreover, the study indicates predominant themes in ownership structure and CSR research and suggests some avenues for future research.
Keywords: 650; Ownership structure; corporate social responsibility; CSR; bibliometric analysis; corporate governance; governance mechanisms